Customers’ Risk Perception and Intention of Using Electronic banking Services: An Empirical Study Based on Evidence of Chinese - Pang, Yingxuan (2020)
With the continuous development of Internet technology, people's life is more and more inseparable from Internet technology. Electronic banking is one of the embodiments of the banking industry in the use of Internet technology. Electronic banking services bring convenience and efficiency to people's lives, and at the same time, risks also follow. As the world's second largest economy and country with the largest population, China's electronic banking user scale exceeds 400 million people, and the annual growth rate of the number of users is more than 10 percent. The risks arising from the use of electronic banking services are also troubling the Chinese people. The purpose of this dissertation is to investigate the impact of perceived risk on customer’s intention to use electronic banking which based on data from China. The model on this dissertation was developed from the traditional Technology Acceptance Model (TAM), new variables in terms of perceived risk and new logical relationship among variables were added in the new theoretical model which proposed in this dissertation. Six dimensions of perceived risk were extract in order to investigate the factors that influence customers’ behavioral intention towards using electronic banking services. The result of this study shows that perceived security risk, financial risk, performance risk, time risk, psychological risk has a significantly and negatively influence customers’ intention towards the use of electronic banking services, and among them, the most concerned by customers is the security risk, and perceived social risk does not influence the intention towards using electronic banking service. In addition, the internal factors of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) also confirmed to be positively influence intention.